Illustrating Finance Policy with Mathematica - Georgakopoulos, Nicholas L. (Quantitative Perspectives on Behavioral Economics and Finance,, 2018)
Students in various disciplines-from law and government to business and health policy-need to understand several quantitative aspects of finance (such as the capital asset pricing model or financial options) and policy analysis (e.g., assessing the weight of probabilistic evidence) but often have little quantitative background. This book illustrates those phenomena and explains how to illustrate them using the powerful visuals that computing can produce. Of particular interest to graduate students and scholars in need of sharper quantitative methods, this book introduces the reader to Mathematica, enables readers to use Mathematica to produce their own illustrations, and places specific emphasis on finance and policy as well as the foundations of probability theory.